Enhancing Professionalism in Zakat Management Through Islamic Competency-Based Human Resource Management: A Literature Review of Key Competencies for Amil Zakat - Nur Aziz (International Journal of Zakat, 2025)
Adequate competencies of zakat officers (amil) significantly impact the overall effectiveness of zakat programs. This study aims to examine the implementation of Islamic Competency-Based Human Resource Management (ICBHRM) in zakat institutions, focusing on identifying key competency dimensions of zakat officers that support professionalism in zakat management. The method employed is a literature review through a systematic analysis of relevant studies from journals, books, and conference papers. Data were collected from academic sources such as Google Scholar and ScienceDirect. The findings suggest that technical, personal, and social competencies serve as the core pillars supporting the professional performance of zakat officers. These competencies play a crucial role in ensuring effective and accountable zakat management. Technical competencies include a deep understanding of zakat jurisprudence, management, and sharia accounting. Meanwhile, personal and social competencies encompass integrity, trustworthiness, and strong interpersonal skills. Zakat officer certification is also considered vital in enhancing the quality of zakat officer performance and the accountability of zakat institutions.This study concludes that implementing ICBHRM in zakat institutions can significantly improve the professionalism and efficiency of zakat management, mainly through applying the core competencies outlined in the Indonesian National Work Competency Standards (SKKNI) and leadership competencies, such as the ability to influence others, develop talent, and provide clear guidance. The discussion of these findings suggests the importance of continuous development through training and certification to ensure zakat officers can compete and adapt to modern management standards without compromising Sharia principles.